The Development of Mobile Applications for Language Learning: A Systematic Review of Theoretical Frameworks - Chuah, Kee Man; Muhammad Kamarul, Kabilan (Society for Research and Knowledge Management, 2022)
This systematic review was conducted to examine theories that were adopted or considered in the development of mobile applications for language learning. It aims to provide a holistic overview of major theoretical principles that underpin each developmental study to identify trends and gaps in the synthesised literature. The studies were collected from the Scopus and Web of Science databases as they were the main sources of reputable journals. Primary searches between 2011 and 2020 revealed approximately 158 studies related to the topic under investigation. After further filtering based on the inclusion criteria and removal of duplicates, 39 studies matched the research criteria and were used for further analysis. The analysis revealed that researchers tend to choose to solve problems pertaining to vocabulary learning and learners’ motivation through the development of mobile applications for language learning. They preferred to use constructivist-based theories such as situated learning and collaborative learning in guiding their development though behaviourist principles are also dominant. However, very few studies used theories related to language acquisition and learning in the design and development process. Hence, this gap should be given priority in future developmental research within the same scope as the generic learning theories may not be accurately addressing the language learning problems.